Resin for use in cement admixture for architectural or civil engineering structures and its manufacturing method

A crosslinked vinyl alcohol polymer with specific properties is used as a cement admixture to address the issue of insufficient water absorption in alkaline environments, effectively suppressing cracks and enhancing the strength of cement-based structures.

JP7605655B2Active Publication Date: 2024-12-24KURARAY CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2021027448
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-02-24
Publication Date
2024-12-24
Estimated Expiration
2041-02-24

AI Technical Summary

Technical Problem

Existing water-absorbing resins used in cement for architectural and civil engineering structures fail to maintain sufficient water absorption in the presence of polyelectrolytes and alkalis, leading to inadequate crack suppression due to capillary tension, especially in concrete and mortar.

Method used

A crosslinked vinyl alcohol polymer with specific cumulative pore volume and pore diameter, containing functional groups, is used as a cement admixture to enhance water absorption and repellency, even in alkaline conditions, thereby suppressing self-shrinkage.

Benefits of technology

The resin effectively supplies water to voids in cement structures, reducing cracks and enhancing the strength of mortar and concrete by maintaining water absorption and repellency, thus improving structural integrity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007605655000001
    Figure 0007605655000001
Patent Text Reader

Abstract

To provide a resin to be blended with cement, excellent in water absorption and syneresis even in the presence of an alkali in cement for a building or a civil engineering structure, thereby exhibiting excellent internal curing effect and capable of suppressing self-shrinkage of mortar and concrete.SOLUTION: The resin to be blended with cement for a building or a civil engineering structure, is composed of a crosslinked vinyl alcohol-based polymer, wherein a cumulative pore volume of pores having a pore diameter of 0.1 to 10 μm is 0.01 to 2.0 mL / g.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin for use in admixture with cement for architectural or civil engineering structures, and a method for producing the same. [Background technology]

[0002] In recent years, the deterioration of infrastructure such as highways and tunnels that were built during the period of high economic growth has become an issue. One of the causes of deterioration of concrete products is acidification caused by rainwater and air seeping through cracks. It is said that cracks in cement used in these architectural and civil engineering structures occur due to the following capillary tension mechanism: 1) In the process of hydration of cement and water, the inside of the hardened body becomes dry and voids are formed. 2) When the voids in this hardened body become unsaturated and an air-liquid interface occurs, a meniscus is formed by the surface tension of the water. 3) Negative pressure is generated in the liquid water, which causes an elastic volume reduction in the hardened body. This volume reduction of cement, or "autogenous shrinkage," is one of the causes.

[0003] In order to suppress the autogenous shrinkage of concrete, it is desirable to increase the amount of water relative to the cement, but in recent years, with the demand for higher strength concrete accompanying the rise in height of reinforced concrete structures and other buildings, the amount of water used has been reduced. However, in concrete with reduced water content, the inside of the voids in particular tends to dry out easily, resulting in significant autogenous shrinkage, which is one of the factors that reduces the strength of buildings.

[0004] Non-Patent Document 1 shows that adding a water-absorbent resin to cement paste can suppress cracks. According to this, it is said that the water-absorbent resin gradually releases the water it holds, reducing capillary tension and suppressing autogenous shrinkage, in response to drying inside the voids caused by the consumption of water during the hydration reaction. Furthermore, after hardening, the water-absorbent resin releases water and shrinks, leaving voids of a size equivalent to the swollen water-absorbent resin, which also has the effect of mitigating the occurrence of cracks caused by the increase in volume due to the freezing of remaining water in concrete or mortar.

[0005] Patent Document 1 discloses that a water-absorbing resin mainly composed of polyacrylic acid gel can be used for architectural or civil engineering structure cement, and Patent Document 3 discloses that a thermally crosslinked modified polyvinyl alcohol resin can be used for excavation cement. However, although polyacrylic acid gel exhibits high water absorption for deionized water or tap water, insolubilization due to ion crosslinking may progress in a polyvalent electrolyte solution containing a large amount of calcium ions, aluminum ions, etc. contained in cement, and the water absorption may be extremely reduced. In addition, modified polyvinyl alcohol resins have a problem in that crosslinking is broken in the alkali of the cement, and they are unable to maintain their water absorption performance until hardening.

[0006] In order to solve such problems, Patent Document 2 discloses that a cationic or amphoteric water-absorbing resin can suppress a decrease in water absorption even when it contains a large amount of polyelectrolytes contained in a cement composition, and can be suitably used as a cement admixture for drilling mud. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] Patent Publication No. 56-069257 [Patent Document 2] WO2017-099082 [Patent Document 3] JP 1-203251 [Non-patent literature]

[0008] [Non-Patent Document 1] Application of Superabsorbent Polymers (SAP) in Concrete Construction: State-of-the-Art Report Prepared by Technical Committee 225-SAP, 2012. Summary of the Invention [Problem to be solved by the invention]

[0009] However, according to the study by the present inventors, the cationic or amphoteric water-absorbing resin shown in Patent Document 2 can retain a large amount of water, but cannot supply sufficient water to the gaps between the water and the hydration product of cement, sand, etc., in the early stage of the hardening process, and therefore cannot relieve the pressure due to capillary tension, and may not be able to exert a sufficient crack suppression effect. The problem that the present invention aims to solve is to provide a cement additive that has an internal curing effect, has a sufficiently high water absorption even in a cement paste under a polyelectrolyte or an alkali, and can supply water to the surroundings during the hardening process. [Means for solving the problem]

[0010] As a result of intensive research aimed at solving the above problems, the inventors have discovered that a resin having a specific cumulative pore volume exhibits water-separation from the resin to the cement, and that by using a resin having a specific crosslinked structure, a sufficient amount of water is absorbed even in the presence of alkali in the cement for architectural or civil engineering structures, and have arrived at the present invention.

[0011] [1] A resin for admixture with cement for architectural or civil engineering structures, comprising a cross-linked vinyl alcohol polymer, the resin having a cumulative pore volume of pores having a pore diameter of 0.1 to 10 μm of 0.01 to 2.0 mL / g. [2] The resin for cement admixture according to [1], wherein the crosslinked structure of the vinyl alcohol-based polymer crosslinked product is derived from a polyaldehyde compound or a polyepoxy compound. [3] The resin for cement admixture according to [1] or [2], wherein the vinyl alcohol polymer crosslinked product contains one or more functional groups selected from the group consisting of a carboxyl group, an ester group, a sulfonic acid group, an amino group, and salts thereof. [4] The resin for cement admixture according to [3], wherein the vinyl alcohol polymer crosslinked product contains one or more carboxylic acid monomer constituent units selected from the group consisting of acrylic acid, methacrylic acid, maleic acid, itaconic acid and derivatives thereof. [5] The resin for admixture with cement according to any one of [1] to [4], wherein the amount of the carboxylic acid monomer constitutional units is 0.1 mol % to 50 mol %. [6] A method for producing a resin for use in cement admixture according to any one of [1] to [5], comprising a step of carrying out a saponification reaction using 1 part by mass or more and 30 parts by mass or less of a vinyl alcohol polymer before saponification per 100 parts by mass of a solvent. [7] A method for producing the resin for cement admixture according to any one of [1] to [4], comprising a step of crosslinking a vinyl alcohol polymer by a heterogeneous reaction. [8] An instant cement comprising the resin for cement admixture according to any one of [1] to [5] and cement. [9] An instant mortar comprising the resin for cement admixture according to any one of [1] to [5], cement, and sand.

[10] An instant concrete comprising the resin for cement admixture according to any one of [1] to [5], cement, sand and stone.

[11] A cement paste comprising the instant cement according to [8] and water.

[12] A fresh mortar comprising the instant mortar according to [9] and water.

[13] A fresh concrete comprising the instant concrete according to

[10] and water.

[14] A mortar comprising the resin for cement admixture according to any one of [1] to [5].

[15] Concrete comprising the resin for cement admixture according to any one of [1] to [5]. Effect of the Invention

[0012] The cement-mixable resin of the present invention has excellent water absorption and water-repellency even in the presence of alkali in the cement for architectural or civil engineering structures, and therefore has a high internal curing effect, that is, can suppress the autogenous shrinkage of mortar or concrete. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] Hereinafter, an embodiment of the present invention will be described, but the present invention is not limited to this embodiment.

[0014] The resin for cement admixture of the present invention has a cumulative pore volume of pores with a pore diameter of 0.1 to 10 μm of 0.01 to 2.0 mL / g. The inventors have studied that the cumulative pore volume of 0.01 mL / g or more provides a large surface area and can hold water that is easily separated from the water in the pores, making it suitable for use as a resin for cement admixture. If the cumulative pore volume exceeds 2.0 mL / g, problems such as formation of coarse aggregates in which particles are fused together during water absorption and easy crushing due to impact during transportation, etc. occur. The cumulative pore volume is preferably 0.1 mL / g or more, more preferably 0.15 mL / g or more, even more preferably 0.2 mL / g or more, and preferably 1.5 mL / g or less, more preferably 1.0 mL / g or less, even more preferably 0.5 mL / g or less.

[0015] The resin for cement admixture satisfying the above range of cumulative pore volume can be controlled by adjusting the concentration of polyvinyl acetate when producing polyvinyl alcohol by saponification of polyvinyl acetate, adjusting the content of auxiliary components in a method of mixing a vinyl alcohol polymer with auxiliary components such as glycerin and ethylene glycol to prepare a dispersion and dissolving the auxiliary components from the dispersion, or adjusting the degree of dispersion of the auxiliary components by adding a dispersant. For example, in the former method, the cumulative pore volume increases by lowering the concentration of polyvinyl acetate in a solvent such as methanol, and decreases by increasing the concentration. The cumulative pore volume can be measured, for example, by mercury intrusion porosimetry, and more specifically, it is a value measured according to the method described in the examples.

[0016] The resin for mixing with cement of the present invention has a particle size that preferably passes through a sieve with a nominal opening of 1000 μm, more preferably passes through a sieve with a nominal opening of 700 μm, even more preferably passes through a sieve with a nominal opening of 500 μm, and particularly preferably passes through a sieve with a nominal opening of 300 μm, preferably does not pass through a sieve with a nominal opening of 10 μm, more preferably does not pass through a sieve with a nominal opening of 30 μm, even more preferably does not pass through a sieve with a nominal opening of 50 μm, and particularly preferably does not pass through a sieve with a nominal opening of 70 μm. In a preferred embodiment, the resin for mixing with cement has a particle size that passes through a sieve with a nominal opening of 1000 μm and does not pass through a sieve with a nominal opening of 10 μm. When the cement-mixed resin has such a particle size, the cement-mixed resin releases water and shrinks after the mortar or concrete hardens, leaving voids of an appropriate size, thereby appropriately exerting the effect of suppressing cracks caused by the freezing and thawing of the water contained in the mortar or concrete.

[0017] In this specification, the term "structural unit" refers to a repeating unit that constitutes a polymer; for example, a vinyl alcohol unit is counted as "1 unit," and a structure in which two vinyl alcohol units are acetalized is counted as "2 units."

[0018] The resin for cement admixture of the present invention is made of a vinyl alcohol polymer crosslinked product from the viewpoint of suppressing the elution of the resin in architectural or civil engineering structure cement. There is no particular limitation on the form of the crosslinked structure, and examples thereof include crosslinked structures by ether bonds, acetal bonds, ester bonds, and carbon-carbon bonds. The presence or absence of a crosslinked structure in a vinyl alcohol polymer can be measured, for example, by the elution rate in hot water or dimethyl sulfoxide at 100°C. Specifically, the presence of a crosslinked structure can be confirmed by the elution rate, which is the ratio of the mass of the eluted sample to the mass of the sample (mass of the eluted sample x 100 / mass of the sample), being a certain value or less (for example, 90 mass% or less).

[0019] An example of the ether bond is an ether bond formed by dehydration condensation between hydroxyl groups of a vinyl alcohol polymer. Another example of the ether bond is an ether bond formed when a polyfunctional epoxy compound having multiple epoxy groups in one molecule is used in the production of a vinyl alcohol polymer. An example of the acetal bond is an acetal bond formed when a polyfunctional aldehyde compound having multiple aldehyde groups in one molecule is used in the production of a vinyl alcohol polymer. An example of the ester bond is an acetal bond formed when a polyfunctional carbonyl compound having multiple carboxyl groups or ester groups in one molecule is used in the production of a vinyl alcohol polymer. Another example of the ester bond is an ester bond formed by dehydration condensation of a carboxyl group and a hydroxyl group of a polyvinyl alcohol polymer, or by ester exchange between an ester group and a hydroxyl group. An example of the carbon-carbon bond is a carbon-carbon bond formed by coupling between carbon radicals of a vinyl alcohol polymer, which occurs when a vinyl alcohol polymer is irradiated with active energy rays. One or more of these crosslinked structures may be included. Among these, a crosslinked structure based on an acetal bond, an ester bond or an ether bond is preferred from the viewpoint of ease of production, and a crosslinked structure based on an acetal bond or an ether bond is more preferred from the viewpoint of the base resistance (elution rate) of the crosslinked structure in cement.

[0020] The crosslinked structure of the vinyl alcohol polymer crosslinked product is preferably derived from a polyhydric aldehyde compound or a polyhydric epoxy compound. Examples of the polyhydric aldehyde compound include bifunctional aldehydes such as glyoxal, malonaldehyde, succinaldehyde, glutaraldehyde, 1,9-nonanedial, adipaldehyde, malealdehyde, tartaraldehyde, citralaldehyde, phthalaldehyde, isophthalaldehyde, and terephthalaldehyde. When a polyhydric aldehyde compound is used, a hydroxyl group of one of the different molecular chains of the vinyl alcohol polymer undergoes an acetalization reaction with one aldehyde group of the polyhydric aldehyde compound, and a hydroxyl group of the other of the two vinyl alcohol polymers undergoes an acetalization reaction with another aldehyde group of the polyhydric aldehyde compound, thereby introducing two acetal bonds. A preferred type of compound is a polyaldehyde compound because of the wide range of solvent options available, and among these, glyoxal, malonaldehyde, succinaldehyde, and glutaraldehyde are more preferred because they can uniformly distribute crosslinks in the resin.

[0021] The amount of crosslinker relative to the hydroxyl groups of the vinyl alcohol polymer that is the raw material for the vinyl alcohol polymer crosslinked product is, from the viewpoint of easily maintaining water absorption in the cement for architectural or civil engineering structures, preferably 0.001 mol % or more, more preferably 0.005 mol % or more, even more preferably 0.01 mol % or more, still more preferably 0.03 mol % or more, and is preferably 0.5 mol % or less, more preferably 0.4 mol % or less, and even more preferably 0.3 mol % or less.

[0022] The content of the vinyl alcohol unit in the vinyl alcohol polymer is preferably 20 mol% or more, more preferably 50 mol% or more, and even more preferably 60 mol% or more, and is preferably 98 mol% or less, more preferably 95 mol% or less, and even more preferably 90 mol% or less, based on the total constitutional units of the vinyl alcohol polymer. The content of the vinyl alcohol unit can be measured by FTIR or solid 13It can be measured by C-NMR, but it can also be calculated from the amount of acetic anhydride consumed when reacting with a certain amount of acetic anhydride.

[0023] The viscosity average degree of polymerization of the vinyl alcohol polymer is not particularly limited, but from the viewpoint of ease of production, it is preferably 20,000 or less, more preferably 10,000 or less, even more preferably 4,000 or less, and particularly preferably 3,000 or less. On the other hand, from the viewpoint of the mechanical properties and resistance to dissolution into water of the vinyl alcohol polymer, the viscosity average degree of polymerization is preferably 100 or more, more preferably 200 or more, and even more preferably 400 or more. The viscosity average degree of polymerization can be measured by a method based on JIS K 6726. When the crosslinked structure has an ether structure, an acetal structure, or an ester structure, the viscosity average degree of polymerization can be measured after the crosslinked structure is cut. The cut can be performed by a general method, for example, a nucleophilic substitution reaction with a strong acid such as hydrobromic acid or hydroiodic acid for an ether structure, a hydrolysis reaction with an acid for an acetal structure, and a hydrolysis reaction with an acid or an alkali for an ester structure, and this operation does not affect the viscosity average degree of polymerization of the vinyl alcohol polymer.

[0024] The vinyl alcohol polymer may contain other structural units besides the vinyl alcohol unit. Examples of the other structural units include structural units derived from monomers for introducing functional groups, which will be described later; structural units derived from vinyl carboxylates, such as vinyl acetate and vinyl pivalate; structural units derived from olefins, such as ethylene, 1-butene, and isobutylene; and the like. The other structural units may contain one type or multiple types.

[0025] The content of the other structural units is preferably 50 mol% or less, more preferably 30 mol% or less, even more preferably 20 mol% or less, even more preferably 10 mol% or less, particularly preferably 5 mol% or less, and preferably 0.1 mol% or more, more preferably 0.5 mol% or more, even more preferably 1 mol% or more, even more preferably 2 mol% or more, particularly preferably 3 mol% or more, based on the total structural units of the vinyl alcohol polymer. When the content of the other structural units is equal to or more than the lower limit and equal to or less than the upper limit, the cement-mixed resin of the present invention is likely to have a better water absorption amount or water absorption rate.

[0026] In one aspect of the present invention, from the viewpoint of expressing water absorption in architectural or civil engineering structure cement, the vinyl alcohol-based polymer crosslinked product preferably has an elution rate in a cement filter solution of 0 to 40%, more preferably 0 to 30%, and even more preferably 0 to 25%. If the elution rate is higher than the upper limit, the effective portion having water absorption capacity is reduced, and the water absorption capacity described below is reduced, so that a large amount of the vinyl alcohol-based polymer crosslinked product needs to be added, or the shape cannot be maintained, resulting in a decrease in the water absorption capacity of the gap. This elution rate is calculated from the weight of the pure content of the vinyl alcohol-based polymer crosslinked product after immersing the vinyl alcohol-based polymer crosslinked product in a cement filter solution at 15 to 25 ° C. for 24 hours and the weight of the vinyl alcohol-based polymer crosslinked product before immersion, and more specifically, is a value measured according to the method described in the Examples. The cement filter solution is an aqueous solution obtained by dispersing 5 parts ion-exchanged water in 1 part ordinary Portland cement by mass, stirring for 24 hours using a magnetic stirrer, and filtering the slurry, as described in Materials and Structures (2018) 51:116. The water absorption and elution behavior in this aqueous solution mimic the behavior of vinyl alcohol polymer cross-linked materials in cement paste.

[0027] In one embodiment of the present invention, from the viewpoint of supplying sufficient water to the surroundings during the curing process, the water absorption capacity of the vinyl alcohol polymer crosslinked product in the cement filter solution is preferably 10 g / g or more, more preferably 15 g / g or more, and particularly preferably 25 g / g or more. If it is lower than 10 g / g, the resin can hold less water, so the amount of water released is also small. On the other hand, from the viewpoint of mechanical strength, such as shape retention during kneading of cement paste, it is preferably 100 g / g or less, more preferably 70 g / g or less, and particularly preferably 40 g / g or less. If it is higher than 100 g / g, there is a concern that the swollen resin cannot maintain its shape when subjected to external pressure during kneading of the cement paste and breaks, resulting in a particle size smaller than the preferred particle size. This water absorption capacity is calculated from the amount of water absorbed after immersing the resin in a cement filter solution at 15 to 25 ° C. for 24 hours and the weight of the resin before immersion, and more specifically, is a value measured according to the method described in the Examples.

[0028] In one embodiment of the present invention, from the viewpoint of supplying sufficient water to the surroundings after curing, the amount of water released per 1 g of the crosslinked vinyl alcohol polymer is preferably 7.0 g or more, more preferably 7.5 g or more, and particularly preferably 8.0 g or more. The amount of water released is calculated from the amount of water released when the water absorbent resin saturated and swollen with a cement filter solution is centrifuged at a predetermined rotation speed, and more specifically, is a value measured according to the method described in the Examples.

[0029] The crosslinked vinyl alcohol polymer desirably contains one or more functional groups selected from the group consisting of a carboxyl group, an ester group, a sulfonic acid group, an amino group, and salts thereof.

[0030] The monomer for introducing the carboxyl group into the cement admixture resin of the present invention is not particularly limited, and examples thereof include carboxylic acids and salts thereof such as acrylic acid, methacrylic acid, maleic acid, itaconic acid, mesaconic acid, citraconic acid, etc. If it is desired to introduce a salt of the carboxyl group, it may be converted into a salt after the carboxyl group is introduced.

[0031] The monomer for introducing the ester group into the vinyl alcohol polymer crosslinked product is not particularly limited, and examples thereof include acrylic esters, anhydrides and neutralized products of carboxylic acid monomers, such as methyl acrylate, methyl methacrylate, monomethyl maleate, dimethyl itaconate, maleic anhydride, dimethyl mesaconic acid, and dimethyl citraconic acid. The ester group may contain lactone generated by dehydration reaction of a hydroxyl group derived from a polyvinyl alcohol polymer and a carboxylic acid ester.

[0032] The monomer for introducing the sulfonic acid group into the vinyl alcohol polymer crosslinked product is not particularly limited, and examples thereof include vinyl sulfonic acid, 2-acrylamido-2-methylpropanesulfonic acid, and p-styrenesulfonic acid. Examples of monomers for introducing a salt thereof include sodium vinylsulfonate, sodium 2-acrylamido-2-methylpropanesulfonate, and sodium p-styrenesulfonate. When it is desired to introduce a salt of a sulfonic acid group, the salt may be converted after the sulfonic acid group is introduced.

[0033] The monomer for introducing the amino group into the vinyl alcohol polymer crosslinked product is not particularly limited, and examples thereof include diallyldimethylammonium chloride, vinyltrimethylammonium chloride, allyltrimethylammonium chloride, p-vinylbenzyltrimethylammonium chloride, and 3-(methacrylamide)propyltrimethylammonium chloride. Examples of the derivatives of the monomers having the ammonium group include the amines of the monomers, and examples of the derivatives include diallylmethylamine, vinylamine, allylamine, p-vinylbenzyldimethylamine, and 3-(methacrylamide)propyldimethylamine.

[0034] Examples of counter cations of the salts of the above functional groups include alkali metal ions such as lithium ion, sodium ion, potassium ion, rubidium ion, and cesium ion; alkaline earth metal ions such as magnesium ion, calcium ion, strontium ion, and barium ion; other metal ions such as aluminum ion and zinc ion; and onium cations such as ammonium ion, imidazolium ions, pyridinium ions, and phosphonium ions.

[0035] The content of the monomer introduced in the crosslinked vinyl alcohol polymer is 0.1 mol% or more, preferably 1 mol% or more, more preferably 3 mol% or more, even more preferably 4 mol% or more, particularly preferably 5 mol% or more, and 50 mol% or less, preferably 40 mol% or less, more preferably 30 mol% or less, even more preferably 25 mol% or less, even more preferably 20 mol% or less, particularly preferably 15 mol% or less, and even more particularly preferably 10 mol% or less. When the content of the functional group is equal to or more than the lower limit, the vinyl alcohol polymer is likely to have a more improved water absorption amount or water absorption rate. When the content of the functional group is equal to or less than the upper limit, the vinyl alcohol polymer is likely to maintain an excellent liquid absorption amount or liquid absorption rate even when in contact with divalent ions contained in cement, and this liquid absorption amount or liquid absorption rate is unlikely to decrease over a long period of time.

[0036] The cement-mixable resin of the present invention desirably contains one or more carboxylic acid monomer constituent units selected from the group consisting of acrylic acid, methacrylic acid, maleic acid, itaconic acid, and derivatives thereof. From the viewpoint of ease of production, methyl acrylate, methyl methacrylate, monomethyl maleate, dimethyl itaconate, and maleic anhydride are preferred.

[0037] The method for producing a resin for cement admixture of the present invention preferably includes a step (A) of carrying out a saponification reaction with 1 to 30 parts by mass of a vinyl alcohol polymer before saponification per 100 parts by mass of a solvent.

[0038] From the viewpoint of production efficiency, the amount of polyvinyl acetate, which is a vinyl alcohol polymer before saponification, used in step (A) is preferably 1 part by mass or more, more preferably 2 parts by mass or more, and more preferably 3 parts by mass or more, relative to 100 parts by mass of the solvent.From the viewpoint of forming pores, it is preferably 30 parts by mass or less, more preferably 20 parts by mass or less, and more preferably 10 parts by mass or less.

[0039] As the type of solvent used in step (A), since the saponification reaction proceeds by transesterification, alcohol solvents such as methanol and ethanol are preferred, and among these, methanol is more preferred from the viewpoint of ease of subsequent removal from the resin.

[0040] The viscosity average degree of polymerization of the polyvinyl acetate used in step (A) is not particularly limited, but from the viewpoint of ease of production, it is preferably 20,000 or less, more preferably 10,000 or less, even more preferably 4,000 or less, and particularly preferably 3,000 or less. On the other hand, from the viewpoint of the mechanical properties and resistance to elution into water of the vinyl alcohol polymer, the viscosity average degree of polymerization is preferably 100 or more, more preferably 200 or more, and even more preferably 400 or more. The viscosity average degree of polymerization of the vinyl alcohol polymer can be measured by a method in accordance with JIS K 6726.

[0041] In step (A), it is preferable to drop a basic compound diluted in a solvent to a desired concentration into a homogeneous solution of polyvinyl acetate. The saponified polyvinyl acetate becomes incompatible with the solvent by this operation and precipitates, making it easy to recover the product.

[0042] In step (A), the moisture content in the system is preferably 0.5% to 1%. If it is lower than 0.5%, the reaction proceeds too quickly and is difficult to control, whereas if it is higher than 1%, the moisture is difficult to remove, and there is a concern that moisture may remain after drying.

[0043] In step (A), when saponification is performed to 98.5 mol% or more, the molar ratio of the basic compound to vinyl acetate is preferably 0.03 to 0.035 mol%. If it is lower than 0.03 mol%, the saponification does not proceed completely, whereas if it is higher than 0.035 mol%, the reaction may proceed too quickly and become difficult to control.

[0044] In step (A), since the saponification reaction is an exothermic reaction, the reaction temperature is preferably 40°C when the basic compound is added, and then increased to 60 to 70°C after visually confirming that the precipitation of polyvinyl alcohol is almost complete.

[0045] The method for producing a resin for cement admixture of the present invention preferably includes a step (B) of crosslinking a vinyl alcohol polymer by a heterogeneous reaction.

[0046] In step (B), by using a heterogeneous reaction, crosslinking can be performed while maintaining the pores of the porous polyvinyl alcohol particles, so that it is easy to obtain a resin for cement admixture in which the total pore volume of pores with a pore diameter of 0.1 to 10 μm is 0.01 to 2.0 mL / g. More specifically, it is preferable to use a heterogeneous reaction in which the raw material vinyl alcohol polymer is dispersed in a solvent in which the vinyl alcohol polymer is insoluble and reacted with a crosslinking agent. The heterogeneous reaction can be determined by visually observing the system in which the crosslinking reaction is taking place, and if particles are observed in the system, it is a heterogeneous reaction.

[0047] In step (B), there can be mentioned (1) a method in which the raw material vinyl alcohol-based polymer is dispersed in a solvent in which the vinyl alcohol-based polymer is insoluble, and reacted with a crosslinking agent dissolved in the solvent, and (2) a method in which the crosslinking agent or a solution in which the crosslinking agent is dispersed is sprayed onto the raw material vinyl alcohol-based polymer, and the crosslinking agent is heated to react with the raw material vinyl alcohol-based polymer.

[0048] In step (B), the method for producing the crosslinked product of the vinyl alcohol polymer is not particularly limited, but method (1) is preferred from the viewpoint of ease of reaction control. For example, when crosslinking with a polyhydric aldehyde is performed, specifically, at least a part of the vinyl alcohol units of a vinyl alcohol polymer produced by a known method can be acetalized with one or more derivatives of a polyhydric aldehyde in the presence or absence of a catalyst, preferably at a reaction temperature of 80° C. or less.

[0049] In step (B), the dispersion medium used is not particularly limited as long as it can swell the vinyl alcohol polymer particles used as a raw material and dissolves at the reaction temperature. From the viewpoint of keeping the vinyl alcohol polymer in a particulate form without dissolving it during the reaction, it is preferable that the dispersion medium contains an organic solvent. The content of the organic solvent in the dispersion medium is preferably 5% by mass or more, more preferably 20% by mass or more, even more preferably 50% by mass or more, even more preferably 70% by mass or more, particularly preferably 80% by mass or more, and may be 100% by mass. When the content of the organic solvent is equal to or more than the lower limit, the fusion of the resin can be suppressed and the shape of the resin can be maintained. On the other hand, it is also a preferred embodiment of the present invention that the content of the organic solvent is 95% by mass or less (more preferably 92% by mass or less, even more preferably 90% by mass or less, particularly preferably 85% by mass or less). When the content of the organic solvent is equal to or less than the upper limit, the polyvinyl alcohol particles are appropriately swollen in the solvent and the carbonyl compound is easily dissolved, so that the polyvinyl alcohol particles tend to be uniformly acetalized even in the interior thereof.

[0050] The organic solvent is not particularly limited, but examples thereof include dialkyl ketones such as acetone and 2-butanone; nitriles such as acetonitrile; alcohols such as methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, 2-butanol, amyl alcohol, isoamyl alcohol, hexanol, cyclohexanol, octanol, and tert-butanol; ethers such as 1,4-dioxane, tetrahydrofuran, 1,2-dimethoxyethane, and diglyme; diol compounds such as ethylene glycol and triethylene glycol; carboxylic acid amides such as acetamide, N,N-dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone; dimethyl sulfoxide, and phenol. Among them, in consideration of the ease of removing the solvent from the modified polyvinyl alcohol resin obtained after the heterogeneous reaction, the solubility of the carbonyl compound and the acid catalyst in the solvent, and the industrial availability of the solvent, the organic solvent is preferably at least one selected from the group consisting of dialkyl ketones, nitriles, alcohols, and ethers, more preferably at least one selected from the group consisting of acetone, 2-butanone, acetonitrile, methanol, ethanol, 1-propanol, 2-propanol, tert-butanol, 1,4-dioxane, and tetrahydrofuran, and even more preferably at least one selected from the group consisting of acetone, 2-butanone, acetonitrile, methanol, 2-propanol, 1,4-dioxane, and tetrahydrofuran. These organic solvents may be used alone or in combination of two or more. The solvent used in the heterogeneous reaction may contain water, but when the solvent used in the heterogeneous reaction does not contain water, the organic solvent is preferably at least one selected from the group consisting of dialkyl ketones, nitriles, alcohols, and ethers, and even more preferably alcohol. As the acetalization reaction proceeds, the interaction between the modified polyvinyl alcohol resin and the solvent changes, so that a solvent may be added during the reaction in order to control the degree of swelling.

[0051] When used as a resin for admixture with cement for architectural or civil engineering structures, the resin may take various forms, including instant cement containing the resin and cement; instant mortar containing the resin, cement, and sand; instant concrete containing the resin, cement, sand, and stones; cement paste containing the resin, cement, and water; fresh mortar containing the resin, cement, sand, and water; fresh concrete containing the resin, cement, sand, stones, and water; mortar containing the resin; and concrete containing the resin.

[0052] The above sand is defined as sand that passes through a 10 mm sieve and 85% or more by weight passes through a 5 mm sieve, and stone is defined as gravel or grinding stone that is retained by 85% or more by weight on a 5 mm sieve.

[0053] When the present invention is used as a resin for admixture with cement for architectural or civil engineering structures, various methods can be used for admixture. For example, a method of directly adding the resin for admixture with cement during the production of cement paste, or a method of adding the resin for admixture with cement that has been swollen with water, can be mentioned.

[0054] Instant cement is a mixture of the resin and cement, and is dry-blended with additives such as adhesives, water-retaining materials, and shrinkage-reducing agents as necessary. Instant mortar is a mixture of the resin, cement, and sand. Instant mortar can be made by mixing each material in any ratio, for example, a dry blend of 1 part cement, 0.004 parts cement admixture resin, and 3 parts sand by volume. Instant concrete is a mixture of the resin, cement, sand, and stones. Instant concrete can be made by mixing each material in any ratio, for example, a dry blend of 1 part cement, 0.004 parts cement admixture resin, 3 parts sand, and 3 to 6 parts stones by volume. The amount of the cement admixture resin is preferably 10 vol% or less, more preferably 1 vol% or less, based on the cement. In addition, either of them may contain additives such as adhesives, water-retaining materials, and shrinkage-reducing agents depending on the purpose, and various cements can be used depending on the purpose, not just ordinary Portland cement.

[0055] The instant cement containing the cement admixture resin and water can be mixed in any ratio, for example, 1.5 to 1.8 parts water to 1 part instant cement by volume. The fresh mortar can be mixed in any ratio, for example, 1 part cement to 3 parts sand and 1.5 to 1.8 parts water by volume, and a mixing ratio of 1 part cement to 2 parts sand is preferable when increasing the adhesive strength. The instant concrete can be mixed in any ratio, for example, 1 part cement to 3 parts sand, 3 to 6 parts stone, and 1.5 to 1.8 parts water by volume, and a mixing ratio of 1 part cement to 2 parts sand and 4 parts stone is preferable when increasing the strength. The cement paste, fresh mortar, and fresh concrete may each contain an admixture such as an adhesive, a water-retaining material, or a shrinkage reducing agent depending on the purpose, and various cements can be used depending on the purpose, not just ordinary Portland cement. The mortar containing the cement admixture resin is one in which the water in the fresh mortar has been partially or entirely consumed by hydration or drying. Furthermore, concrete containing the cement admixture resin is fresh concrete in which the water has been partially or entirely consumed by hydration reactions or drying.

[0056] Furthermore, the instant cement, instant mortar, instant concrete, cement paste, fresh mortar, fresh concrete, mortar and concrete of the present invention may contain additives within the range that does not impair the effects of the present invention.Examples of additives include additives that are generally used for mixing with cement, such as expansion agents, quick-setting agents, high-strength admixtures, silica fume, waterproofing agents, air-entraining agents, water-reducing agents, air-entraining water-reducing agents, high-performance water-reducing agents, high-performance air-entraining water-reducing agents, superplasticizers, hardening accelerators, setting retarders, foaming agents, non-separating admixtures in water, hydration heat inhibitors, rod-binding agents, drying shrinkage reducing agents, and cold resistance agents, as well as polysaccharides such as starch, modified starch, sodium alginate, chitin, chitosan, cellulose and its derivatives; polyethylene, polypropylene, ethylene-propylene copolymers, polystyrene, acrylonitrile-styrene. copolymers, acrylonitrile-butadiene-styrene copolymers, polyvinyl chloride, polycarbonate resins, polyethylene terephthalate, polybutylene terephthalate, polylactic acid, polysuccinic acid, polyamide 6, polyamide 6·6, polyamide 6·10, polyamide 11, polyamide 12, polyamide 6·12, polyhexamethylenediamine terephthalamide, polyhexamethylenediamine isophthalamide, polynonamethylenediamine terephthalamide, polyphenylene ether, polyoxymethylene, polyethylene glycol, polypropylene Resins such as ethylene glycol, polytrimethylene glycol, polytetramethylene glycol, polyurethane, polyvinyl alcohol, ethylene-vinyl alcohol copolymer, polyvinyl acetate, ethylene-vinyl acetate copolymer, polyacrylic acid, polyacrylic acid ester, polyacrylate, polymethacrylic acid, polymethacrylic acid ester, polymethacrylate, ethylene-acrylic acid copolymer, ethylene-acrylic acid ester copolymer, ethylene-acrylate copolymer, ethylene-methacrylic acid copolymer, ethylene-methacrylate ester copolymer, and ethylene-methacrylate copolymer; rubbers and elastomers such as natural rubber, synthetic isoprene rubber, chloroprene rubber, silicone rubber, fluororubber, urethane rubber, acrylic rubber, styrene-based thermoplastic elastomer, olefin-based thermoplastic elastomer, ester-based thermoplastic elastomer, urethane-based thermoplastic elastomer, and amide-based thermoplastic elastomer; clay minerals such as kaolinite, smectite, montmorillonite, sericite, chlorite, glauconite, talc, natural zeolite, and synthetic zeolite; and sand.These may be used alone or in combination of two or more kinds.

[0057] The mixing method can be by hand using a kneading boat or a construction wheelbarrow, by using a concrete mixer, by using a mixer truck, etc. Cement, sand, and stones can be mixed, water can be added, and the cement admixture resin can be added in powder form to the mixture, or the resin in powder form can be made to absorb some water in advance to swell and then added.

[0058] The method can be applied not only to a general method of pouring cement paste into a formwork, but also to shotcrete. There is no particular restriction on the type of cement to which the method can be applied, and the method can be applied to Portland cement such as ordinary Portland cement, high-early-strength Portland cement, moderate-heat Portland cement, and white Portland cement, as well as to special cements such as blast-furnace cement, silica cement, and fly ash cement.

[0059] The resin for cement admixture of the present invention exhibits excellent water absorption and water release properties as a cement admixture, and is therefore suitable for use in architectural and civil engineering structures. Examples of architectural structures in which the resin for cement admixture of the present invention is used include buildings, houses, stadiums, etc. Examples of civil engineering structures include viaducts for expressways and trains, tunnels, slopes for expressways, dams, roads, harbors, etc. EXAMPLES

[0060] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples in any way.

[0061] (Measurement method)

[0062] (1) Preparation of cement filter solution The aqueous solution was prepared by dispersing 150 g of ordinary Portland cement manufactured by Taiheiyo Cement Corporation in 750 g of ion-exchanged water, stirring the slurry for 24 hours using a magnetic stirrer, and filtering the resulting slurry. The pH of the cement filter solution was measured at 22°C using a pH meter manufactured by Horiba Ltd., and was found to be 12.54 to 12.79. The solution prepared by this method was used in the measurements (3) to (5) below.

[0063] (2) Cumulative pore volume 0.25 g of the resin obtained in the examples and comparative examples was placed in a standard 5 cc powder cell (stem volume 0.4 cc) and measured using a Micromeritics pore size distribution analyzer (Shimadzu Corporation, Autopore 9520) under an initial pressure of 2.5 kPa. The mercury parameters were a mercury contact angle of 130 degrees and a mercury surface tension of 485 hynes / cm.

[0064] (3) Elution rate The classified 100μ~212μm cement-mixing resin and a nylon mesh tea bag (size: 7cm×12cm, mesh size: 57μm) with three sides sealed were dried at 40℃ overnight under reduced pressure (0.67MPa). The tare weight of the tea bag was measured, 0.2g of cement-mixing resin was placed in the tea bag, and the remaining side was heat-sealed. The tea bag was immersed in 500mL of cement filter solution at 22℃ for 24 hours, after which the tea bag was removed and dried again at 40℃ under reduced pressure (0.67MPa) in a vacuum dryer overnight. The resin was removed from the tea bag and the weight was measured, and the elution rate was calculated using the following formula. Four tea bags were prepared for each type of resin and tested, and the average value was used. (Elution rate [%]) = 100 × [{(Weight of resin before immersion in cement filter solution [g]) - (Weight of resin after immersion in cement filter solution and drying [g])} / (Weight of resin before immersion in cement filter solution [g])] However, the elution rate was not calculated for samples whose weight after drying increased due to weight increase caused by counter cation substitution of the resin or weight increase caused by precipitation of calcium carbonate on the resin surface after immersion in the cement filter solution.

[0065] (4) Water absorption capacity The calculation was performed according to the method described in Materials and Structures (2018) 51:116. As in the leaching rate measurement in (3), the tea bag and cement-mixed resin were dried and immersed in the cement filter solution, and then the removed tea bag containing the cement-mixed resin was placed on a paper rag for 30 seconds to remove excess water. The weight was measured and used as the weight of the wet resin and tea bag. The water absorption capacity was then calculated according to the following formula. As in the leaching rate test in (3), the average value of four samples was used in this test as well. (Water absorption capacity [g / g]) = {(Weight of wet resin and tea bag [g]) - (Weight of tea bag and dry resin before immersion in cement filter solution [g]) - (Amount of liquid absorbed by tea bag [g])} / (Weight of dry resin [g]) The amount of liquid absorbed by the tea bag was calculated by drying the same tea bag as above at 40℃ overnight under reduced pressure (0.67MPa), immersing it in the cement filter solution for 30 seconds, removing it, placing it on a paper cloth for 30 seconds to remove excess water, and then measuring its weight and calculating it according to the following formula. This test was performed on 10 tea bags, and the average value was used. (Amount of liquid absorbed by tea bag [g]) = (Weight of wet tea bag [g]) - (Weight of tea bag before immersion in cement filter solution [g])

[0066] (5) Amount of water released per gram of resin About 3 g of the 100 μm to 300 μm cement-mixing resin was immersed in a cement filter solution in excess of the amount of water absorption capacity obtained in (4), left to stand for 16 hours, and then filtered through a nylon mesh with a mesh size of 57 μm to produce a gel. A 10 μm membrane filter sandwiched between two sheets of nonwoven fabric was packed into a 3 mL plastic syringe, and 3 mL of the gel was taken and added, followed by centrifugation at 2200 rpm. The water separation rate was calculated from the proportion of the cement filter solution (flowing solution) that flowed out at this time, as shown below, and the amount of water separated per 1 g of resin was calculated using the following formula. (Amount of solution in gel [g]) = (Weight of gel [g]) - {(Weight of gel [g]) ÷ (Water absorption capacity calculated in (3) [g / g])} (Syneresis rate [%]) = (amount of solution flowing out [g]) / (amount of solution in the gel [g]) × 100 (Amount of water released per 1 g of resin [g]) = (1 g of resin [g]) × (water absorption capacity calculated in (3) [g / g]) × (water release rate [%]) In the above, the gel weight is the weight [g] of 3 mL of gel.

[0067] [Production Example 1] Into a reactor equipped with a stirrer, a reflux condenser, a nitrogen inlet, and an initiator addition port, 9030 g of vinyl acetate, 18.15 g of methyl acrylate, and 3810 g of methanol were introduced, and the inside of the reactor was replaced with inert gas for 30 minutes while bubbling with nitrogen. The temperature of the reactor was started to rise using a water bath, and when the internal temperature of the reactor reached 60°C, 2.40 g of azobisisobutyronitrile (AIBN) was added as an initiator to start polymerization. Sampling was performed appropriately, and the progress of polymerization was confirmed from the solid content concentration, and the consumption rate, which is the total mass of vinyl acetate and methyl acrylate consumed by polymerization relative to the total mass of vinyl acetate and methyl acrylate introduced, was calculated. When the consumption rate reached 4% by mass, the internal temperature of the reactor was cooled to 30°C to stop the polymerization. The reactor was connected to a vacuum line, and the remaining vinyl acetate was distilled off under reduced pressure at 30°C together with methanol. While visually checking the inside of the reactor, when the viscosity increased, methanol was appropriately added and distillation was continued, and polyvinyl acetate containing 5.2 mol % of acrylic acid-derived structural units was obtained. The content of acrylic acid-derived structural units was 5.2 mol %. 13 Measurements were performed using C-NMR. Next, 360 g of the obtained polyvinyl acetate containing acrylic acid-derived structural units and 6552 g of methanol were added to the same reactor as above, and the polyvinyl acetate containing acrylic acid-derived structural units was dissolved. The reactor was heated using a water bath, and the reactor was heated with stirring until the internal temperature reached 70°C. 280.8 g of a methanol solution of sodium hydroxide (metacaustic, concentration 15% by mass) was added thereto, and saponification was carried out at 70°C for 2 hours. The solution after saponification was filtered and vacuum dried at 40°C to obtain 165 g of polyvinyl alcohol (hereinafter referred to as polyvinyl alcohol (a)). The viscosity average degree of polymerization of the obtained polyvinyl alcohol (a) was 1700, the degree of saponification was 99.5 mol%, and the content of acrylic acid-derived constitutional units was 5.2 mol%.

[0068] [Production Example 2] A polymerization vessel (continuous polymerization apparatus) equipped with a reflux condenser, a raw material supply line, a thermometer, a nitrogen inlet, and an agitator, and an apparatus equipped with a reflux condenser, a raw material supply line, a reaction liquid withdrawal line, a thermometer, a nitrogen inlet, and an agitator were used. Vinyl acetate (VAM) (656 L / H), methanol (MeOH) (171 L / H), a 20% methanol solution of monomethyl maleate (MMM) as a modified species (101 L / H), and a 2% methanol solution of 2,2'-azobis (4-methoxy-2,4-dimethylvaleronitrile) (AMV) as an initiator (25 L / H) were continuously fed into the polymerization vessel using a metering pump. The polymerization liquid was continuously withdrawn from the polymerization vessel so that the liquid level in the polymerization vessel was constant. The polymerization rate of vinyl acetate in the polymerization liquid withdrawn from the polymerization vessel was adjusted to 40%. The residence time in the polymerization vessel was 4 hours. The temperature of the polymerization liquid withdrawn from the polymerization vessel was 63°C. The polymerization liquid was taken out of the polymerization tank, and unreacted vinyl acetate was removed by introducing methanol vapor into the polymerization liquid, thereby obtaining a methanol solution of polyvinyl acetate (PVAc) (concentration: 35%). A desired amount of water and methanol were added to the above-mentioned polyvinyl acetate methanol solution to prepare a polyvinyl acetate (PVAc) / methanol solution (concentration 32% by mass) with a water content of 1.3% by mass, which is a saponification raw material solution. A sodium hydroxide / methanol solution (concentration 4% by mass) as a saponification catalyst solution was added so that the molar ratio of sodium hydroxide to the vinyl acetate unit in the above-mentioned PVAc was 0.10. The saponification raw material solution and the saponification catalyst solution were mixed using a static mixer. The resulting mixture was placed on a belt and held for 18 minutes under a temperature condition of 40°C to allow the saponification reaction to proceed. The gel obtained by the saponification reaction was crushed and dewatered. The obtained polyvinyl alcohol powder was continuously fed to a dryer with a jacket temperature of 105°C at 600 kg / hr. The average residence time of the powder in the dryer was 4 hours. Then, crushing was performed to obtain polyvinyl alcohol (b). The resulting polyvinyl alcohol (b) had a viscosity average degree of polymerization of 1200, a degree of saponification of 96.0 mol %, and a content of monomer units having two carboxyl groups of 4.0 mol %.

[0069] [Example 1] In a three-necked separable flask equipped with a reflux condenser and agitator, 445.5 g of methanol, 47.4 g of pure water, 1.206 g of 25 mass% glutaraldehyde aqueous solution (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.), and 150 g of polyvinyl alcohol (a) were introduced and stirred at 23°C to disperse polyvinyl alcohol (a). A mixture of 5.66 g of 47 mass% sulfuric acid aqueous solution and 3 g of pure water was added dropwise over 10 minutes, and the temperature was raised to 65°C to carry out a crosslinking reaction for 6 hours. After the reaction, the polymer was removed by filtration, and the filtered polymer was washed by dispersing it in 220 g of methanol, stirring for 30 minutes, and filtering. Washing was repeated 7 times. The washed polymer was introduced into a three-necked separable flask equipped with a reflux condenser and a stirring blade, and 245 g of methanol, 40.8 g of pure water, and 24.35 g of 50% by mass potassium hydroxide were added and reacted at 65°C for 2 hours. After the reaction, the polymer was taken out by filtration, and then the filtered polymer was dispersed in 330 g of methanol, stirred for 30 minutes, and filtered for washing. Washing was repeated 7 times. The washed polymer was vacuum dried at 40°C for 12 hours to obtain the intended cement admixture resin. The content of acrylic acid-derived constituent units relative to the total constituent units of the resin was 5.2 mol%. The obtained cement admixture resin was subjected to the above-mentioned tests (2) to (5) and each measurement was performed. The results are shown in Table 1.

[0070] [Example 2] Into a three-necked separable flask equipped with a reflux condenser and agitator, 445.5 g of methanol, 47.4 g of pure water, 1.206 g of 25 mass% glutaraldehyde aqueous solution, and 150 g of polyvinyl alcohol (a) were introduced, and the mixture was stirred at 23°C to disperse the polyvinyl alcohol. A mixture of 5.66 g of 47 mass% sulfuric acid aqueous solution and 3 g of pure water was added dropwise over 10 minutes, and the mixture was heated to 65°C to carry out a crosslinking reaction for 6 hours. After the reaction, the polymer was taken out by filtration, and the polymer thus taken out was dispersed in 220 g of methanol, stirred for 30 minutes, and filtered to perform washing. Washing was repeated seven times. The washed polymer was vacuum-dried at 40°C for 12 hours to obtain the intended resin for cement admixture. The above-mentioned tests (2) to (5) were carried out on the obtained resin, and each measurement was carried out. The results are shown in Table 1.

[0071] [Comparative Example 1] The target resin for cement admixture was obtained and measured in the same manner as in Example 1, except that polyvinyl alcohol (a) was changed to polyvinyl alcohol (b) and the amount of 25% by mass glutaraldehyde aqueous solution was changed to 1.118 g. The results are shown in Table 1.

[0072] [Comparative Example 2] 500 g of polyvinyl alcohol (b) was weighed out in a recovery flask and heat-treated at 130°C under reduced pressure for 5 hours using an evaporator to carry out a crosslinking reaction, obtaining the target resin for cement admixture, which was then measured. The amount of water released per 1 g of resin could not be measured because the resin dissolved in the cement filter solution when preparing the sample. The results are shown in Table 1.

[0073] [Comparative Example 3] The above-mentioned tests (2) to (5) were carried out using AQUAKEEP 10-SHPF (acrylic acid-sodium acrylate copolymer cross-linked product) manufactured by Sumitomo Seika Chemicals Co., Ltd. as a general-purpose water-absorbent resin, and each measurement was carried out. The results are shown in Table 1.

[0074] [Table 1]

[0075] As shown in Examples 1 and 2, the vinyl alcohol polymer crosslinked product satisfying the cumulative pore volume of the present invention exhibits a low elution rate and a high water absorption capacity in a cement filter solution, i.e., an alkaline aqueous solution, and exhibits water-repelling properties that are believed to correlate with crack suppression of concrete in architectural or civil engineering structures. On the other hand, Comparative Example 1, which uses a different saponification process and has a small cumulative pore volume, exhibited almost no water-repelling properties. When the crosslinking method was different (Comparative Example 2), the gel strength was low and a water-repelling test could not be performed. In addition, when a general-purpose water-absorbent resin was used (Comparative Example 3), it was unable to absorb almost any cement solution and did not exhibit a water-repelling effect. [Industrial Applicability]

[0076] The resin for admixture with cement for architectural or civil engineering structures of the present invention has excellent water-repelling properties, and can therefore supply sufficient water to voids caused by volumetric shrinkage due to the hydration reaction of cement and water, thereby suppressing cracks caused by autogenous shrinkage, and can therefore be suitably used to improve the strength of mortar and concrete.

Claims

1. A resin for use in cement admixture for architectural or civil engineering structures, comprising a cross-linked vinyl alcohol polymer, The vinyl alcohol-based polymer crosslinked product is obtained by reacting a vinyl alcohol-based polymer with a crosslinking agent, the vinyl alcohol polymer has a viscosity average degree of polymerization of 400 or more and 3,000 or less, the content of structural units other than vinyl alcohol units relative to all structural units in the vinyl alcohol polymer is 3 mol % or more and 20 mol % or less, and the content of structural units derived from monomers introducing one or more functional groups selected from the group consisting of a carboxyl group, an ester group, a sulfonic acid group, an amino group, and salts thereof is 3 mol % or more and 10 mol % or less, the crosslinking agent is one or more polyaldehyde compounds selected from the group consisting of glyoxal, malonaldehyde, succinaldehyde, and glutaraldehyde; the amount of the crosslinker relative to the hydroxyl group of the vinyl alcohol polymer is 0.001 mol % or more and 0.5 mol % or less, A resin for cement admixture, having a cumulative pore volume of pores having a pore diameter of 0.1 to 10 μm of 0.01 to 2.0 mL / g.

2. The resin for cement admixture according to claim 1, wherein the crosslinked vinyl alcohol polymer contains one or more functional groups selected from the group consisting of a carboxyl group, an ester group, a sulfonic acid group, an amino group, and salts thereof.

3. The resin for cement admixture according to claim 2, wherein the vinyl alcohol-based polymer crosslinked product contains one or more carboxylic acid-based monomer constituent units selected from the group consisting of acrylic acid, methacrylic acid, maleic acid, itaconic acid, and derivatives thereof.

4. The method for producing a resin for cement admixture according to any one of claims 1 to 3, comprising a step of carrying out a saponification reaction with 1 part by mass or more and 30 parts by mass or less of a vinyl alcohol-based polymer before saponification per 100 parts by mass of a solvent.

5. The method for producing the resin for cement admixture according to any one of claims 1 to 3, comprising a step of crosslinking a vinyl alcohol polymer by a heterogeneous reaction.

6. An instant cement comprising the resin for cement admixture according to any one of claims 1 to 3 and cement.

7. An instant mortar comprising the resin for cement admixture according to any one of claims 1 to 3, cement and sand.

8. An instant concrete comprising the resin for cement admixture according to any one of claims 1 to 3, cement, sand and stones.

9. A cement paste comprising the instant cement of claim 6 and water.

10. A fresh mortar comprising the instant mortar according to claim 7 and water.

11. A fresh concrete comprising the instant concrete of claim 8 and water.

12. A mortar comprising the resin for cement admixture according to any one of claims 1 to 3.

13. A concrete comprising the resin for cement admixture according to any one of claims 1 to 3.

Citation Information

Patent Citations

  • Cement composition

    JP1981069257A

  • Cement admixture and composition

    JP1989203251A

  • Polyvinyl alcohol powder

    JP1997316272A

  • Autogenous shrinkage reducing agent

    JP2011246286A

  • Water-absorbing resin, and agricultural water retention material

    JP2019119891A